Laminated structure and semiconductor device
A laminated structure with a carbon-doped crystalline oxide film having a corundum structure addresses the roughness and defect issues of α-gallium oxide films, resulting in improved semiconductor characteristics and performance.
Patent Information
- Application Number
- JP2024150923
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2025-01-08
- Estimated Expiration
- 2039-08-28
AI Technical Summary
Existing methods for forming α-gallium oxide thin films for semiconductor devices result in films with rough surfaces and impaired semiconductor characteristics, and surface treatments like etching can further damage the films.
A laminated structure is developed with a crystalline oxide film having a corundum structure, doped with carbon impurities, achieving a root mean square roughness of 0.1 μm or less, and a manufacturing method involving thermal reaction of raw material fine particles with a carrier gas and a surface smoothing agent to enhance surface smoothness.
The laminated structure achieves a smoother surface and improved semiconductor properties, reducing crystal defects and enhancing the performance of semiconductor devices.
Smart Images

Figure 2025001669000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminated structure, a semiconductor device, and a method for manufacturing the laminated structure. [Background technology]
[0002] As a method for forming a highly crystalline gallium oxide-based thin film on a sample to be deposited, a deposition technique using water particles such as a mist CVD method is known (Patent Document 1). In this method, a gallium compound such as gallium acetylacetonate is dissolved in an acid such as hydrochloric acid to prepare a raw material solution, and the raw material solution is atomized to generate raw material particles, which are then supplied to the deposition surface of the sample to be deposited by a carrier gas, and the raw material mist is reacted to form a thin film on the deposition surface, thereby forming a highly crystalline gallium oxide-based thin film on the sample to be deposited.
[0003] In order to form a semiconductor device using a gallium oxide-based thin film, it is essential to control the electrical conductivity of the gallium oxide-based thin film. Patent Document 1 and Non-Patent Document 1 disclose a technique for doping an α-gallium oxide thin film with an impurity. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2013-28480 A [Patent Document 2] JP 2015-199649 A [Non-Patent Document 1] Electrical Conductive Corundum-Structured α-Ga2O3 Thin Films on Sapphire with Tin-Doping Grown by Spray-Assisted Mist Chemical Vapor Deposition(Japanese Journal of Applied Physics 51 (2012) 070203) Summary of the Invention [Problem to be solved by the invention]
[0005] According to the methods of Patent Document 1 and Non-Patent Document 1, a thin film of α-gallium oxide (hereinafter, sometimes referred to as "α-Ga2O3") having excellent electrical conductivity can be formed, but there is a particular problem that the film surface is not smooth, and it is still not satisfactory for use in semiconductor devices. In addition, in order to smooth the film surface, it is possible to perform surface treatment such as etching, but in this case, there are problems such as the thin film being scraped off or the semiconductor properties being impaired.
[0006] To address this problem, Patent Document 2 discloses a method for reducing the average roughness (Ra). However, even when this method is used, the surface flatness is still not sufficient, and the characteristics of the semiconductor device using the obtained film are also unsatisfactory.
[0007] The present invention has been made to solve the above problems, and aims to provide a laminated structure that includes a crystalline oxide film having a corundum structure with a smooth surface and that has excellent semiconductor properties when applied to a semiconductor device, and further to provide a laminated structure that has a crystalline oxide film with reduced crystal defects, and to provide a method for manufacturing the laminated structure. [Means for solving the problem]
[0008] The present invention has been made to achieve the above-mentioned object, and provides a laminated structure having a base substrate and a crystalline oxide film having a corundum structure, wherein the crystalline oxide film contains at least carbon (C) as an impurity, and the root mean square roughness (RMS) of the crystalline oxide film is 0.1 μm or less.
[0009] Such a laminated structure has a crystalline oxide film with a smooth surface, and when applied to a semiconductor device, the semiconductor properties are excellent.
[0010] At this time, the C concentration in the crystalline oxide film is 2×10 17 ~2×10 20 / cm 3 It is possible to provide a laminated structure in which
[0011] This makes the surface smoother, and when applied to a semiconductor device, the semiconductor properties are improved.
[0012] In this case, the layered structure can have a thickness of the crystalline oxide film of 1 μm or more.
[0013] This results in a thick-film laminated structure having a smooth surface.
[0014] In this case, the underlying substrate may be a c-plane sapphire substrate to form a laminate structure.
[0015] This results in a laminated structure having a crystalline oxide film with a better quality corundum structure.
[0016] At this time, the area of the crystalline oxide film is 100 mm 2 A laminated structure as described above can be obtained.
[0017] This allows for a larger area which is more useful for semiconductor devices.
[0018] In addition, a method for manufacturing a laminated structure can be provided, in which raw material fine particles generated by atomizing a raw material solution are transported to a substrate by a carrier gas, and the raw material fine particles are thermally reacted on the substrate to form a crystalline oxide film having a corundum structure, in which a surface smoothing agent containing at least carbon (C) is mixed into the raw material solution to perform a C doping process on the crystalline oxide film, and the root mean square roughness (RMS) of the surface of the crystalline oxide film is set to 0.1 μm or less.
[0019] According to such a method for manufacturing a laminated structure, a laminated structure can be manufactured that includes a crystalline oxide film having a corundum structure with a smooth surface, and that has excellent semiconductor characteristics when applied to a semiconductor device.
[0020] In this case, the method for producing the laminated structure may use at least one of alcohols and diketones as the surface smoothing agent.
[0021] This makes it possible to more effectively and stably manufacture a laminated structure having a smoother surface.
[0022] Furthermore, the present invention provides a laminate structure including a first crystalline oxide film having a corundum structure and a second crystalline oxide film having a corundum structure, the first crystalline oxide film being disposed on the second crystalline oxide film, and the second crystalline oxide film containing at least carbon (C) as an impurity.
[0023] In such a laminated structure, the surface of the second crystalline oxide film having a corundum structure is smooth, so that the crystal defects of the first crystalline oxide film having a corundum structure are reduced, and the laminated structure has very excellent semiconductor properties.
[0024] At this time, the C concentration in the second crystalline oxide film is 2×10 17 ~2×10 20 / cm 3 It is possible to provide a laminated structure in which
[0025] This makes the surface smoother, and when applied to a semiconductor device, the semiconductor properties are improved.
[0026] In this case, the first crystalline oxide film may have a thickness of 1 μm or more. 2 A laminated structure as described above can be obtained.
[0027] This makes the semiconductor device more useful.
[0028] In this case, a semiconductor device including the above-mentioned laminated structure can be obtained.
[0029] This results in a semiconductor device with excellent characteristics. Effect of the Invention
[0030] As described above, the laminate structure of the present invention has a crystalline oxide film having a corundum structure with a smooth surface, and when applied to a semiconductor device, the laminate structure has excellent semiconductor properties. Also, according to the method for manufacturing the laminate structure of the present invention, it is possible to manufacture a laminate structure having a crystalline oxide film having a corundum structure with a smooth surface, and when applied to a semiconductor device, the laminate structure has excellent semiconductor properties. Furthermore, the laminate structure of the present invention includes a crystalline oxide film having a corundum structure with reduced crystal defects in the film, and when applied to a semiconductor device, the laminate structure has excellent semiconductor properties. [Brief description of the drawings]
[0031] [Figure 1] 1 is a schematic diagram showing an example of a film forming apparatus used in a film forming method according to the present invention; [Diagram 2] 1 is a schematic diagram showing an example of a laminated structure according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0032] The present invention will be described in detail below, but the present invention is not limited thereto.
[0033] As described above, there has been a need to provide a laminate structure which includes a crystalline oxide film having a corundum structure with a smooth surface and which has excellent semiconductor properties when applied to a semiconductor device, a method for manufacturing the laminate structure, and a laminate structure which includes a crystalline oxide film having a corundum structure with reduced crystal defects in the film and which has excellent semiconductor properties when applied to a semiconductor device.
[0034] As a result of extensive investigations into the above-mentioned problems, the inventors have discovered that a layered structure having a base substrate and a crystalline oxide film having a corundum structure, wherein the crystalline oxide film contains at least carbon (C) as an impurity and the root mean square roughness (RMS) of the crystalline oxide film is 0.1 μm or less, has a crystalline oxide film with a smooth surface, and becomes a layered structure with excellent semiconductor properties when applied to a semiconductor device, thereby completing the present invention.
[0035] The inventors have also discovered that a method for manufacturing a laminated structure, which involves atomizing a raw material solution to produce raw material fine particles, transporting the raw material fine particles to a substrate using a carrier gas, and thermally reacting the raw material fine particles on the substrate to form a crystalline oxide film having a corundum structure, can be used to manufacture a laminated structure having a crystalline oxide film with a smooth surface, by mixing a surface smoothing agent containing at least carbon (C) into the raw material solution to dope the crystalline oxide film with C, and making the root mean square roughness (RMS) of the surface of the crystalline oxide film 0.1 μm or less, and have completed the present invention.
[0036] Furthermore, the inventors have discovered that a laminate structure including a first crystalline oxide film having a corundum structure and a second crystalline oxide film having a corundum structure, the first crystalline oxide film being disposed on the second crystalline oxide film, the second crystalline oxide film containing at least carbon (C) as an impurity, provides a crystalline oxide film with reduced crystal defects in the film, and results in a laminate structure with excellent semiconductor properties when applied to a semiconductor device, thereby completing the present invention.
[0037] The following description will be given with reference to the drawings.
[0038] As a result of intensive research to achieve the above-mentioned object, the inventors discovered that a crystalline layered structure having a smooth surface of a crystalline oxide film can be obtained by doping treatment using a surface smoothing agent, and after further research, they have completed the present invention.
[0039] According to a first aspect of the present invention, there is provided a crystalline laminated structure comprising a base substrate and a crystalline oxide film having a corundum structure provided thereon, either directly or via another layer, wherein the root mean square roughness (RMS) of the crystalline oxide film is 0.1 μm or less.
[0040] Furthermore, according to a second aspect of the present invention, there is provided a crystalline laminated structure comprising at least a first crystalline oxide film having a corundum structure and a second crystalline oxide film having a corundum structure, the first crystalline oxide film being provided on the second crystalline oxide film, and the second crystalline oxide film containing at least carbon (C) as an impurity.
[0041] The root mean square roughness (RMS) is not particularly limited as long as it is 0.1 μm or less, but is preferably 30 nm or less, and more preferably 10 nm or less. The root mean square roughness (RMS) refers to a value calculated based on JIS B0601 (corresponding to Rq in the standard) using the surface shape measurement results for a 10 μm square area by an atomic force microscope (AFM).
[0042] The laminated structure according to the present invention is a structure containing one or more crystalline oxide films. For example, it may be a laminate of one or more crystalline oxide films and a base substrate or a thin film. It may also contain a film (layer) other than the crystalline oxide film (e.g., an amorphous layer). It may also be a laminate consisting of multiple films (layers) from which the base substrate has been removed.
[0043] The crystalline oxide film may be annealed, so that a metal oxide film formed by oxidizing the ohmic electrode may be formed between the crystalline oxide film and the ohmic electrode. Examples of the ohmic electrode include indium and titanium.
[0044] The base substrate is not particularly limited as long as it can be a support for the crystalline oxide film. The material is not particularly limited, and a known substrate can be used, and it may be an organic compound or an inorganic compound. Examples of the substrate include polysulfone, polyethersulfone, polyphenylene sulfide, polyetheretherketone, polyimide, polyetherimide, fluororesin, metals such as iron, aluminum, stainless steel, and gold, silicon, sapphire, quartz, glass, calcium carbonate, gallium oxide, SiC, ZnO, and GaN, but are not limited thereto. In the laminated structure according to the present invention, a substrate having a corundum structure is preferable. Examples of the substrate having a corundum structure include a sapphire substrate (e.g., a c-plane sapphire substrate) and an α-type gallium oxide substrate. In particular, it is preferable to use a c-plane sapphire substrate. This is because a crystalline oxide film having a better quality corundum structure can be obtained. The thickness of the base substrate is not particularly limited, but is preferably 10 to 2000 μm, more preferably 50 to 800 μm. The area of the substrate is preferably 100 mm 2 The aperture (diameter) is preferably 2 inches (50 mm) or more, and more preferably 2 inches (50 mm) or more.
[0045] The crystalline oxide film is not particularly limited as long as it is a thin film having a corundum structure and containing an oxide semiconductor as a main component. The crystalline oxide film is preferably a single crystal, but may be a polycrystal. The composition of the crystalline oxide film is preferably such that the total atomic ratio of gallium, indium, aluminum and iron in the metal elements contained in the film is 0.5 or more, and more preferably the atomic ratio of gallium in the metal elements is 0.5 or more. Specifically, this preferred atomic ratio is, for example, 0.5, 0.6, 0.7, 0.8, 0.9, 1, and may be within the range between any two of the numerical values exemplified here. In the present invention, it is more preferable that the atomic ratio of gallium in the metal elements is 0.5 or more, because the function of the surface smoothing agent in the raw material solution can be more suitably expressed and the surface roughness of the crystalline oxide film can be further reduced.
[0046] The composition of the crystalline oxide film is, for example, represented by the general formula: In X Al Y Ga Z Fe V O3 (0≦X≦2.5, 0≦Y≦2.5, 0≦Z≦2.5, 0≦V≦2.5, X+Y+Z+V=1.5 to 2.5) is preferable, and 1≦Z is more preferable. In this general formula, specific examples of preferable X, Y, Z and V are 0, 0.01, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.1, 2.2, 2.3, 2.4, and 2.5, respectively. In addition, preferred X+Y+Z+V are, for example, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.1, 2.2, 2.3, 2.4, and 2.5. The X, Y, Z, and V, as well as X+Y+Z+V, may each be within a range between any two of the numerical values exemplified here. The above general formula expresses the composition of atoms on the lattice points forming the corundum structure, and as is clear from the fact that it is not written as "X+Y+Z+V=2", it may also include non-stoichiometric oxides, which may also include metal-deficient oxides and oxygen-deficient oxides.
[0047] The crystalline oxide film may be formed directly on the base substrate, or may be formed via another layer. The other layer may be a crystalline film having a corundum structure of another composition, a crystalline film other than a corundum structure, or an amorphous film. For example, a laminated structure may be formed in which a crystalline oxide film not doped with C is interposed between a crystalline oxide film doped with C and having a smoothed surface and a base substrate.
[0048] The crystalline oxide film is preferably doped with impurities at least in a part thereof (more specifically, in a part in the thickness direction), and may have a single-layer structure or a multi-layer structure. In the case of a multi-layer structure, the crystalline oxide film is formed, for example, by laminating an insulating thin film and a conductive thin film, but the present invention is not limited to this. In addition, when an insulating thin film and a conductive thin film are laminated to form a multi-layer structure, the compositions of the insulating thin film and the conductive thin film may be the same or different from each other. The thickness ratio of the insulating thin film and the conductive thin film is not particularly limited, but for example, the ratio of (thickness of the conductive thin film) / (thickness of the insulating thin film) is preferably 0.001 to 100, and more preferably 0.1 to 5. More preferred ratios are, for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 3, 4, 5, and may be within a range between any two of the numerical values exemplified here.
[0049] The conductive thin film may be doped with impurities for imparting conductivity. By appropriately adjusting the conductivity, a crystalline oxide semiconductor film can be obtained. The doping concentration of the impurities for imparting conductivity is appropriately determined depending on the characteristics required for the conductive thin film, but is preferably 1×10 15 / cm 3 From 1×10 22 / cm 3 The type of impurity to be doped is not particularly limited, but examples thereof include at least one dopant selected from Ge, Sn, Si, Ti, Zr, Hf, V, Nb, Rh, Ag, and Cu. Although doping of an impurity is not usually required for an insulating thin film, it may be doped to the extent that electrical conductivity is not exhibited.
[0050] The thickness of the crystalline oxide film is not particularly limited and may be 1 μm or less or 1 μm or more, but in the present invention, the thickness of the crystalline oxide film is preferably 1 μm or more, and more preferably 1 to 50 μm. By setting the thickness to such a preferable thickness, not only can the surface smoothness be improved without impairing the semiconductor properties, but also the electrical resistance can be reduced during annealing treatment, resulting in better semiconductor properties.
[0051] The laminated structure of the present invention is manufactured by atomizing a raw material solution to produce raw material fine particles, supplying the raw material fine particles to a film formation chamber by a carrier gas to form a crystalline oxide film having a corundum structure on a base substrate placed in the film formation chamber, and doping the crystalline oxide film with a surface smoothing agent to reduce the surface roughness of the crystalline oxide film, that is, the root mean square roughness (RMS), to 0.1 μm or less.
[0052] 1 shows an example of a film forming apparatus 101 that can be used to manufacture a laminated structure according to the present invention. The film forming apparatus 101 includes a mist generating section 120 that generates mist by misting a raw material solution, a carrier gas supplying section 130 that supplies a carrier gas for carrying the mist, a film forming section 140 that heat-treats the mist to form a film on a substrate, and a transporting section 109 that connects the atomizing section 120 and the film forming section 140 and transports the mist by the carrier gas. The film forming apparatus 101 may be controlled in operation by including a control section (not shown) that controls the entire or part of the film forming apparatus 101. Details of the film forming apparatus 101 will be described in the following examples.
[0053] More specifically, the crystalline oxide film can be formed by supplying raw material fine particles generated from a raw material solution in which raw material compounds are dissolved to a film formation chamber and reacting the raw material compounds in the film formation chamber. The solvent of the raw material solution is preferably water or hydrogen peroxide solution. When impurity doping is performed on a thin film, the raw material compounds may be thermally reacted in the presence of a dopant raw material. The dopant raw material is preferably included in the raw material solution and is microparticulated together with the raw material compounds. In this application, in addition to n-type dopants and p-type dopants for expressing conductivity, elements that bring about a surface smoothing effect are also referred to as dopants.
[0054] The method of forming the crystalline oxide film is not particularly limited, but for example, the crystalline oxide film can be formed by thermally reacting a raw material compound in which one or more metals selected from gallium compounds, iron compounds, indium compounds, aluminum compounds, vanadium compounds, titanium compounds, chromium compounds, rhodium compounds, iridium compounds, nickel compounds, and cobalt compounds are combined according to the composition of the crystalline oxide film. This allows the crystal growth of the crystalline oxide film from the base substrate side on the base substrate. The above metal compounds may be organometallic complexes (e.g., acetylacetonato complexes, carbonyl complexes, ammine complexes, and hydride complexes) or halides (fluorides, chlorides, bromides, or iodides) of each metal, or may be compounds that are made by using metallic gallium or metallic indium as a starting material and changing them into gallium compounds and indium compounds just before film formation. In addition, metallic gallium dissolved in an acid such as hydrochloric acid or hydrobromic acid can also be used as the gallium compound.
[0055] Furthermore, an acid may be mixed into the raw material solution. Examples of the acid include hydrogen halides such as hydrobromic acid, hydrochloric acid, and hydroiodic acid, halogen oxo acids such as hypochlorous acid, chlorous acid, hypobromous acid, bromous acid, hypoiodous acid, and iodic acid, formic acid, and nitric acid. In addition, a base may be mixed into the raw material solution. Examples of the base include potassium hydroxide, sodium hydroxide, ammonia, calcium hydroxide, barium hydroxide, magnesium hydroxide, copper hydroxide, and iron hydroxide. Among them, ammonia is particularly preferable in that it has a low boiling point and does not leave a residue when the solution is heated.
[0056] In the laminated structure and the method for manufacturing the laminated structure according to the present invention, the doping treatment is carried out by including a surface smoothing agent in the raw material solution. By carrying out the doping treatment by including a surface smoothing agent in the raw material solution, it is possible to efficiently and industrially advantageously manufacture a crystalline laminated structure having a crystalline oxide film with a surface roughness of 0.1 μm or less.
[0057] The surface smoothing agent is not particularly limited as long as it can make the root mean square roughness (RMS) of the crystalline oxide film 0.1 μm or less, but in the method for producing a laminated structure according to the present invention, it is preferably an organic compound, and more preferably an alcohol or a diketone. A laminated structure having a smoother surface can be produced more effectively and stably. Here, examples of alcohols include methanol, ethanol, and propanol, as well as diols such as ethylene glycol, propylene glycol, and diethylene glycol, and triols such as glycerin, and any of these may be used. Examples of diketones include diacetyl, acetylacetone, 2,5-hexanedione, and dimedone, and any of these may be used.
[0058] When alcohol or diketone is used as a surface smoothing agent, C is introduced into the film, suppressing the deterioration of surface roughness. It is thought that C has the effect of relaxing lattice distortion by entering between the crystal lattices. It is also thought that the molecules of the surface smoothing agent induce steric hindrance on the substrate surface, promoting planar crystal growth.
[0059] The surface smoothing agent may be added directly to the aqueous solution in which the raw material compound is dissolved, or the surface smoothing agent may be dissolved in water in advance and the pH adjusted, and then the surface smoothing agent may be added to the aqueous solution in which the raw material compound is dissolved.
[0060] In the laminated structure according to the present invention, the C content in the crystalline oxide film is 2×10 17 ~2×10 20 (atoms / cm 3 ), preferably 3 × 10 17 ~1×10 20 (atoms / cm 3 ), and more preferably 4×10 17 ~8×10 19 (atoms / cm 3 ) is most preferred.
[0061] In the method for producing a laminated structure according to the present invention, it is most preferable to use methanol or acetylacetone as the surface smoothing agent, and by using methanol or acetylacetone, the surface of a crystalline oxide film containing α-Ga2O3 as a main component can be made extremely smooth. The amount of the surface smoothing agent added is not particularly limited, but is preferably 10% or less by volume in the raw material solution, more preferably 7% or less, and most preferably within the range of 3 to 0.001%. By using it in such a preferable range, it can function as a surface smoothing agent, and the surface of the crystalline oxide film can be made smooth.
[0062] Examples of dopant raw materials for imparting electrical conductivity to a crystalline oxide film include metal elements or compounds (e.g., halides, oxides, hydroxides) of impurities to be doped. For controlling electronic conductivity, n-type dopants such as Ge, Sn, Si, Ti, Zr, Hf, V, and Nb, and p-type dopants such as Cu, Ir, Rh, Sn, and Ag can be used, but are not limited to these.
[0063] The thermal reaction is not particularly limited as long as the raw material fine particles react by heating. The reaction conditions can be appropriately set according to the raw material and the film to be formed. For example, the heating temperature can be in the range of 100 to 600°C, preferably in the range of 200°C to 600°C, and more preferably in the range of 300°C to 550°C.
[0064] The thermal reaction may be carried out under any of the following atmospheres: vacuum, non-oxygen atmosphere, reducing gas atmosphere, air atmosphere, and oxygen atmosphere, and may be appropriately set depending on the film to be formed. The reaction pressure may be under any of atmospheric pressure, pressurized pressure, and reduced pressure, but film formation under atmospheric pressure is preferred because the apparatus configuration can be simplified.
[0065] The crystalline oxide film having a root mean square roughness (RMS) of 0.1 μm or less as described above can be used as a buffer layer. That is, a first crystalline oxide film is formed on a substrate having a second crystalline oxide film having a root mean square roughness (RMS) of 0.1 μm or less formed thereon. Since the surface of the second crystalline oxide film is flat, defects and dislocations in the film formed on this film are significantly reduced. If the obtained first crystalline oxide film is used in a semiconductor device, a semiconductor device having excellent semiconductor characteristics can be obtained. The C concentration in the second crystalline oxide film is 2×10 17 ~2×10 20 (atoms / cm 3 On the other hand, the C concentration in the first crystalline oxide film is not particularly limited. That is, the C concentration in the first crystalline oxide film is preferably 2×10 17 ~2×10 20 (atoms / cm 3) or 2 × 10 17 (atoms / cm 3 ) or less. This is because C is necessary for realizing surface flatness, but is not particularly necessary for realizing excellent semiconductor properties.
[0066] The crystalline oxide according to the present invention may be annealed after film formation. The temperature of the annealing is not particularly limited, but is preferably 600° C. or less, more preferably 550° C. or less, and most preferably 500° C. or less. By performing the annealing at such a preferred temperature, the electrical resistance of the crystalline oxide film can be more suitably reduced. The treatment time of the annealing is not particularly limited, but is preferably 10 seconds to 10 hours, and more preferably 10 seconds to 1 hour.
[0067] In the laminated structure according to the present invention, the crystalline oxide film may be peeled off from the base substrate. The peeling means is not particularly limited and may be a known means. Examples of the peeling means include a means for peeling off by applying a mechanical shock, a means for peeling off by applying heat and using thermal stress, a means for peeling off by applying vibration such as ultrasonic waves, and a means for peeling off by etching. By the peeling, the crystalline oxide film can be obtained as a free-standing film.
[0068] (Example of the configuration of a crystalline laminated structure) FIG. 2 shows a preferred example of a laminated structure according to the present invention and a semiconductor device using the same. In the example of FIG. 2, a crystalline oxide film 203 is formed on an undersubstrate 201. The crystalline oxide film 203 is configured by laminating an insulating thin film 203a and a conductive thin film 203b in this order from the undersubstrate 1 side. A gate insulating film 205 is formed on the conductive thin film 203b. A gate electrode 207 is formed on the gate insulating film 205. In addition, source-drain electrodes 209 are formed on the conductive thin film 203b so as to sandwich the gate electrode 207. With this configuration, it is possible to control the depletion layer formed in the conductive thin film 203b by the gate voltage applied to the gate electrode 207, and a transistor operation (FET device) is possible.
[0069] Examples of semiconductor devices formed using the stacked structure according to the present invention include transistors and TFTs such as MIS, HEMT, and IGBT, Schottky barrier diodes using semiconductor-metal junctions, PN or PIN diodes combined with other P layers, and light-emitting and receiving elements. The stacked structure according to the present invention is useful for improving the characteristics of these devices. EXAMPLES
[0070] The present invention will be described in detail below with reference to examples, but the present invention is not limited thereto.
[0071] Example 1 The film forming apparatus 101 used in this embodiment will be described with reference to Fig. 1. The film forming apparatus 101 includes a hot plate 108 on which a substrate 110, which is a sample to be filmed such as a base substrate, is placed and heated, carrier gas sources 102a and 102b for supplying carrier gas, flow rate control valves 103a and 103b for controlling the flow rate of the carrier gas sent from the carrier gas sources 102a and 102b, a particle generating source 104 in which a raw material solution 104a is stored, a container 105 in which water 105a is stored, an ultrasonic vibrator 106 attached to the bottom surface of the container 105, and a film forming chamber 107 made of quartz. By making the film forming chamber 107 out of quartz, it is possible to prevent impurities originating from the apparatus from being mixed into the thin film formed on the substrate 110.
[0072] An aqueous solution of gallium bromide and tin chloride was prepared so that the atomic ratio of tin to gallium was 1:0.05. The concentration of gallium bromide was 0.1 mol / L. In order to promote the dissolution of tin chloride, 10% by volume of 48% hydrobromic acid solution was added. Furthermore, 0.016% of methanol was mixed in as a surface smoothing agent.
[0073] As the substrate 110, a c-plane sapphire substrate having a diameter of 4 inches (100 mm) was placed on a hot plate 108 and heated to raise the substrate temperature to 500° C. Next, flow rate control valves 103a and 103b were opened to supply carrier gas from carrier gas sources 102a and 102b into the film formation chamber 107, and after the atmosphere in the film formation chamber 107 was sufficiently replaced with the carrier gas, the total flow rate of the carrier gas was adjusted to 26 L / min. Oxygen gas was used as the carrier gas.
[0074] Next, the ultrasonic vibrator 106 was vibrated at 2.4 MHz, and the vibration was propagated to the raw material solution 104a through the water 105a to atomize the raw material solution 104a and generate raw material fine particles. The raw material fine particles were introduced into the film formation chamber 107 by the carrier gas, and a thin film was formed on the film formation sample 110 by a CVD reaction on the film formation surface of the film formation sample 110. The film formation time was 180 minutes.
[0075] The phase of the thin film formed was identified. Identification was performed by performing 2θ / ω scanning at angles of 15 degrees to 95 degrees using a thin film XRD diffractometer. Measurements were performed using CuKα radiation. As a result, the formed thin film was α-Ga2O3 having a corundum structure. In addition, the thickness of the thin film of this example was measured using an interference type thickness meter, and the thickness was 6.0 μm.
[0076] (Comparative Example) The film was formed without mixing methanol into the raw material solution. Specifically, an aqueous solution of 0.1 mol / L gallium bromide was prepared so that the atomic ratio of tin chloride to gallium was 1:0.05, and 10% by volume of 48% hydrobromic acid solution was added. Aside from using this as the raw material solution, the film was formed in the same manner as in Example 1. As a result of evaluation, it was confirmed that the film was α-Ga2O3 having a corundum structure, and the film thickness was 5.8 μm.
[0077] (Reference example 2) As the raw material solution, an aqueous solution of 0.02 mol / L gallium iodide and tin chloride was prepared so that the atomic ratio of tin to gallium was 1:0.007, and 2% of 35% hydrochloric acid solution was added by volume. Furthermore, 0.003% of methanol was mixed as a surface smoothing agent. Aside from using this as the raw material solution, a film was formed in the same manner as in Example 1. As a result of evaluation, it was confirmed that the film was α-Ga2O3 having a corundum structure, and the film thickness was 1.3 μm.
[0078] Example 3 As a raw material solution, metallic gallium was dissolved in hydrochloric acid to prepare a solution with a gallium concentration of 0.05 mol / L. In response to this, an aqueous solution of tin chloride was adjusted so that the atomic ratio of tin to gallium was 1:0.01, and 1% by volume of 35% hydrochloric acid solution was contained. Furthermore, 0.008% of methanol was mixed as a surface smoothing agent. Aside from using this as the raw material solution, a film was formed in the same manner as in Example 1. As a result of evaluation, it was confirmed that the film was α-Ga2O3 having a corundum structure, and the film thickness was 3.1 μm.
[0079] Example 4 The film was formed using ethanol instead of methanol in Example 1. Other than this, the film was formed in the same manner as in Example 1. As a result of evaluation, it was confirmed that the film was α-Ga2O3 having a corundum structure, and the film thickness was 6.1 μm.
[0080] Example 5 In Example 1, oxalic acid was used instead of methanol to form a film. Other than this, a film was formed in the same manner as in Example 1. As a result of evaluation, it was confirmed that the film was α-Ga2O3 having a corundum structure, and the film thickness was 6.3 μm.
[0081] Example 6 The film was formed by using acetylacetone instead of methanol in Example 1. Other than this, the film was formed in the same manner as in Example 1. As a result of evaluation, it was confirmed that the film was α-Ga2O3 having a corundum structure, and the film thickness was 6.0 μm.
[0082] Example 7 In Example 6, the concentration of acetylacetone was set to 2.9%, and the film was formed in the same manner as in Example 1. As a result of evaluation, it was confirmed that the film was α-Ga2O3 having a corundum structure, and the film thickness was 5.9 μm.
[0083] Example 8 An acetylacetone-ammonia aqueous solution was prepared in advance so that the molar ratio of acetylacetone:ammonia was 1:1. This aqueous solution was used as acetylacetone in Example 7 to form a film. Other than this, a film was formed in the same manner as in Example 1. As a result of evaluation, it was confirmed that the film was α-Ga2O3 having a corundum structure, and the film thickness was 6.4 μm.
[0084] Example 9 Except for changing the deposition time to 20 minutes, deposition was performed in the same manner as in Example 1. As a result of evaluation, it was confirmed that the film was α-Ga2O3 having a corundum structure, and the film thickness was 0.55 μm.
[0085] (evaluation) The root mean square surface roughness (RMS) of the α-Ga2O3 thin film samples obtained in Examples 1, 3 to 9, Reference Example 2, and Comparative Example was measured using an atomic force microscope (AFM). The C content in the film was also examined using SIMS. The results are shown in Table 1.
[0086] [Table 1]
[0087] As shown in Table 1, the sample that did not use a surface smoothing agent had large irregularities, whereas the sample that used a surface smoothing agent showed an RMS value of several nm, indicating that the film had excellent surface smoothness. At the same time, the C concentration in the film became extremely high, which is thought to have brought about the surface smoothing effect.
[0088] Example 10 Except for the film formation time being 10 minutes, the film was formed in the same manner as in Example 1, and the obtained film was used as the second crystalline oxide film. Subsequently, the raw material solution was changed to one not containing methanol, and film formation was performed, and an α-Ga2O3 film was formed to a thickness of 5.4 μm as the first crystalline oxide film. X-ray diffraction measurement was performed on the obtained sample to evaluate the crystallinity. Specifically, the rocking curve of the (0006) plane diffraction peak of α-Ga2O3 was measured, and its full width at half maximum was obtained. The obtained full width at half maximum was 11 seconds, and it was confirmed that the film had excellent crystallinity.
[0089] The present invention is not limited to the above-described embodiment. The above-described embodiment is merely an example, and anything that has substantially the same configuration as the technical idea described in the claims of the present invention and exhibits similar effects is included in the technical scope of the present invention. [Explanation of symbols]
[0090] 101...film forming apparatus, 102a...carrier gas source, 102b...dilution carrier gas source; 103a...flow rate control valve; 103b...flow rate control valve, 104...particle source, 104a...raw material solution, 105...container, 105a...water, 106...ultrasonic transducer, 107...film formation chamber, 108...hot plate; 109...transport unit; 109a...supply pipe; 110...substrate (crystalline substrate), 112...exhaust port, 116...oscillator, 120... atomization section, 130... carrier gas supply section, 140... film formation section, 201...underlying substrate, 203...crystalline oxide film, 203a...insulating thin film, 203b...conductive thin film, 205...gate insulating film, 207...gate electrode, 209...Source / drain electrode.
Claims
1. A laminated structure including a first crystalline oxide film having a corundum structure and a second crystalline oxide film having a corundum structure, The first crystalline oxide film is disposed on the second crystalline oxide film, the first and second crystalline oxide films contain a metal element therein, and the atomic ratio of gallium in the metal element is 0.5 or more; the second crystalline oxide film contains at least carbon (C) as an impurity, The C concentration in the second crystalline oxide film is 7.1×10 17 ~2×10 20 / cm 3 and A laminated structure, wherein the first crystalline oxide film contains a dopant.
2. A laminated structure including a first crystalline oxide film having a corundum structure and a second crystalline oxide film having a corundum structure, The first crystalline oxide film is disposed on the second crystalline oxide film, the first and second crystalline oxide films contain a metal element therein, and the atomic ratio of gallium in the metal element is 0.5 or more; the second crystalline oxide film contains at least carbon (C) as an impurity, The C concentration in the second crystalline oxide film is 7.1×10 17 ~2×10 20 / cm 3 and A laminated structure characterized in that the first crystalline oxide film is formed by thermally reacting raw material fine particles produced by atomizing a raw material solution on the second crystalline oxide film having a surface root mean square roughness (RMS) of 0.1 μm or less.
3. 3. The laminate structure according to claim 1, wherein the first crystalline oxide film has a thickness of 1 [mu]m or more.
4. The area of the first crystalline oxide film is 100 mm 2 The laminated structure according to any one of claims 1 to 3, characterized in that
5. 5. The laminate structure according to claim 1, wherein the second crystalline oxide film has a thickness of 6 μm or less.
6. 6. The laminated structure according to claim 1, further comprising an underlying substrate, the underlying substrate being a c-plane sapphire substrate.
7. A semiconductor device comprising the laminated structure according to any one of claims 1 to 6.
Citation Information
Patent Citations
Crystalline laminated structure and semiconductor device
JP2015196603A
Crystalline laminated structure and semiconductor device
JP2015199648A
α-Ga2O3 SINGLE CRYSTAL, PRODUCTION METHOD OF α-Ga2O3, AND SEMICONDUCTOR DEVICE USING THE SAME
JP2016155714A
Crystalline oxide semiconductor film and method for manufacturing the same
JP2018002544A
High-crystallinity conductive alpha type gallium oxide thin film with dopant added, and method of forming the same
JP2013028480A